Social media intelligence - Moe, Wendy; Schweidel, David A., 1981- (Cambridge : Cambridge University Press, 2014)
In the world of Facebook, Twitter and Yelp, water-cooler conversations with co-workers and backyard small talk with neighbors have moved from the physical world to the digital arena. In this new landscape, organizations ranging from Fortune 500 companies to government agencies to political campaigns continuously monitor online opinions in an effort to guide their actions. Are consumers satisfied with our product? How are our policies perceived? Do voters agree with our platform? Measuring online opinion is more complex than just reading a few posted reviews. Social media is replete with noise and chatter that can contaminate monitoring efforts. By knowing what shapes online opinions, organizations can better uncover the valuable insights hidden in the social media chatter and better inform strategy. This book can help anyone facing the challenge of making sense of social media data to move beyond the current practice of social media monitoring to more comprehensive use of social media intelligence.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Consumers -- Research; Social media; Marketing -- Social aspects; Internet marketing -- Social aspects